What can social work seek and find in the area of civil society? - Gojová, Vendula (Wydawnictwo Uniwersytetu Rzeszowskiego, 2015)
From the changes which have occurred in society roughly over the last four decades, and the associated problems of development (Dahrendorf 1991; Esping-Andersen 2002; Giddens 2004; Keller 2009; Keller 2011) we can select the following phenomena in regard to the topic of this text – (1) people are constrained in their possibilities to ensure their own existence, (2) the globalised market increasingly meets the needs of communities less. We can identify various reactions and recommendations as to this state of society and the related crisis of the welfare state. One of the solution strategies may oscillate between proposals by Rosanvallon (Keller 2009) and Giddens (2004). It means solutions developed in a parallel way in the civil society space, in a space which should be close to social work. In the first part of this text we will try to discuss what in this area seems to be important for social work as an agent of social change. Of main importance is the second part which suggests the possible inter-disciplinary collaboration of social work and social entrepreneurship, which could support the potential of civil society. All this aims at answering the question of whether social work could use ideas of social entrepreneurship, resting exactly on this potential, to achieve its goals. And if so, what form its intervention might take.
Keywords: civil society; social inclusion; social work